Comparative Performance Of Soybean Varieties Under Environmental Conditions Of Tandojam, Pakistan. (Plant Bulletin, 2024)
The experiment carried out during 2021–22, aimed to compare the performance of different soybean varieties under the environmental conditions of Tandojam. The treatments included T1 = Ajmeri, T2 = Rawal, and T3 = NARC-1. The soybean Rawal ranked first with a 64.00 cm plant height, 4.60 m2 leaf area index, 0.29 g seed weight, 7610 kg ha-1 biological yield, 3666 kg ha-1 seed yield, and 48.17% harvest index. Ajmeri variety significantly and ranked 2nd with 58.49 cm plant height, 4.21 m2 leaf area index, 0.23 g seed weight, 7129 kg ha-1 biological yield, 3268 kg ha-1 seed yield, and 46.18% harvest index. The soybean variety NARC-1 ranked least in performance with 56.31 cm plant height, 3.79 m2 leaf area index, 0.17 g seed weight, 7000 kg ha-1 biological yield, 3233 kg ha-1 seed yield, and a 45.84% harvest index. From the presented study, it was concluded that of the soybean varieties evaluated in this study, the variety Rawal (48.17 kg ha-1) showed better overall performance and maximum yield as compared to Ajmeri (46.18 kg ha-1) and NARC-1 (45.84 kg ha-1). However, the newly developed variety Rawal excelled in yield traits and demonstrated promising performance, indicating its potential as a future variety.
Keywords: Soybean, temperature treatments, heat stress, crop management